Prolegomena to the Linguo-semiotic Study of Advertising Discourse - G. Kurenova, Daria; V. Olyanitch, Andrew; E. Pavlovskaya, Olga; S. Sakhno , Olga (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of the study is due to the globalization of consumer requests for quality awareness of products and services, which imposes responsibility on the product promoters for the semiotic accuracy of the advertising discourse. In this regard, this article is aimed at identifying clusters of signs and concepts used in the advertising discourse to achieve the maximum impact on the consumer and increase his/her awareness. The leading approach to the linguo-semiotic study of the advertising discourse is the use of the algorithm “from sign to word and to discourse.". It makes it possible to comprehensively consider the cognitive and linguo-semiotic mechanisms of discourse development and apply the method of studying this process to the study of advertising communication space. The article presents prolegomena to a large-scale study of the semiotics of advertising communication in general: The article reveals the prospects and shows the vectors of five stages of the linguo-semiotic research of advertising discourse development, such as identifying clusters of signs that support the institutional characteristics of advertising discourse; identifying directions for the typology of advertising discourse signs; and determining clusters of signs supporting the conceptual sphere of advertising communication. The paper shows the direction and stages of the formation of values among the consumers of modern advertising discourse and determines the stratagems that form the strategic component of the advertising discourse. Already at this (initial) stage of a largescale study of the linguo-semiotics of advertising discourse, a typology of sign clusters has been made: 1) maintaining the institutional characteristics of advertising discourse (legislative signs, fixative signs, restrictive signs, gluttonyms, personal signs, phononyms, actionyms, locatives, attractives, chrononyms, auditives); 2) vectorization of the functions of the advertising discourse in the following directions: a) informative (informative signs); b) imperative (imperatives or impact signs); c) axiological (axionyms); d) argumentative (argumentative signs); 3) ensuring the semiotisation of the advertising message through the promotion of the basic concepts of “State”, “Action” and “Process” and their specifying concepts, for example, the concept of “Beauty” (somatism signs, coloronyms, condition signs, luxonyms, exclusive signs); 4) semiotisation of the process of value creation by the advertising discourse through the formation of a technological and comfortable environment (technonyms, ecologems) and a call for a healthy lifestyle through “shocking advertising” or “shockvertising” (aggravatives, epiciniums); 5) incarnations of the advertising impact (stratagems - positionyms [differentiation signs, signs of value orientation, signs of assignment of estimated values], signs of optimization [stratagems-coordinatives, stratagems-cognitonyms, stratagems-attractors, stratagems-mnemonyms, stratagems-argumentative signs; discriminative stratagems], signs-technonyms). The materials of the article are of practical value for linguistic specialists in the field of linguo-semiotics, cognitive linguistics, conceptology, for theorists and practitioners in advertising, marketing and impact technologies, public relations.